POSTPARTUM INSERTION OF INTRAUTERINE CONTRACEPTIVE DEVICE: A SAFE AND EFFECTIVE CONTRACEPTION - Fatima, Saher; Rehman, Anjum; Ahmed, Zeeshan; Sajid, Muhammad Maaz; Habiba, umme; Rehman, Ambreen (Journal of Ayub Medical College Abbottabad, 2022)
Background: The incidence of maternal mortality and morbidity related to the termination of unwanted pregnancy in Pakistan is rising at an alarming rate. Instant Postpartum insertion of intra- uterine contraceptive device (PPIUCD) is an effective contraceptive measure to reduce unexpected pregnancy and its associated complications in developing countries like Pakistan. Methods: The current study was conducted in a public sector hospital in Karachi with a total of 7314 pregnant women counselled for insertion of PPIUCD antenatally. Out of which 5682 women agreed to the insertion and 1632 refused the procedure, mostly due to unfamiliarity with PPIUCD insertion. PPIUCD was inserted within 48 hours of delivery in 1441 patients and they were followed for 6 months onwards. Results: Total postpartum insertions were 1441 which was found to be an effective measure with the continuation rate of 91% among 785 followed up cases. Postpartum IUCD insertion was found as an effective, satisfactory and convenient practice for the women of developing countries like Pakistan, to get an on-time appropriate contraceptive measure. Conclusion: PPIUCD was found to have high retention and low expulsion rate and its efficacy can be improved further by proper training and skills of healthcare professionals. In this regard, appropriate strategies should be formulated and implemented at the statutory level by increasing social awareness and practice of using PPIUCD by health care providers to reduce undesired pregnancies.